2011
DOI: 10.1007/s00774-011-0339-8
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism of femoral neck cross-sectional bone geometry in athletes and non-athletes: a hip structural analysis study

Abstract: The characterisation of bone geometry in male and female athletes may increase our understanding of how physical loading may enhance bone strength in both sexes. This study investigated sexual dimorphism in hip geometry of athletes and age- and sex-matched non-athletes. Dual energy X-ray absorptiometry of the left proximal femur was performed in 62 male (n = 31; 30.2 ± 4.6 years) and female (n = 31; 27.9 ± 5.2 years) competitive endurance runners, and 36 male (n = 18; 28.7 ± 5.8 years) and female (n = 18; 29.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…One study reported greater bone strength estimates using HSA in 18-to 35-year-old athletes versus nonathletes but did not compare amenorrheic with eumenorrheic athletes (4). There are also limited data in adolescence and young adulthood, a time critical for bone accrual toward attainment of peak bone mass.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One study reported greater bone strength estimates using HSA in 18-to 35-year-old athletes versus nonathletes but did not compare amenorrheic with eumenorrheic athletes (4). There are also limited data in adolescence and young adulthood, a time critical for bone accrual toward attainment of peak bone mass.…”
Section: Discussionmentioning
confidence: 97%
“…Hip structural analysis (HSA) is a technique that uses the properties of dual energy x-ray absorptiometry (DXA) images to derive geometric parameters for the hip that are associated with bone strength (4). This is a validated technique to assess hip bone geometry, which avoids the significant radiation associated with QCT at this site.…”
mentioning
confidence: 99%
“…Research elsewhere however, suggests that HSA is superior in both young adult women and men athletes, with women athletes demonstrating greater strength indices than non-athletic men (23). HSA was utilised to derive values of bone geometry.…”
Section: Discussionmentioning
confidence: 99%
“…HSA derives strength parameters for the hip using properties of DXA images (11). This validated technique allows assessment of hip bone geometry while avoiding radiation associated with QCT at this site.…”
mentioning
confidence: 99%